PROSPECTS AND CHALLENGES OF ONLINE EDUCATION DEVELOPMENT IN UKRAINE - Shcherbachenko, Viktoriia; Sliusarenko, Anna Diana (Socio-economic relations in the digital society, 2023)
The article presents the findings of the study of the prospects and challenges for the development of online education in Ukraine. The aim of the study is to identify prospects for the development of the online education sector in Ukraine, as well as to detect the constraints that affect the slowdown in the evolution of online education in Ukraine. In order to achieve the defined purpose, the following objectives need to be realised: to consider the reasons for the transition to online learning, to analyse the latest research related to online education both in Ukraine and abroad, to determine the weaknesses and strengths of online education in Ukraine, to examine the prospects for the development of online education in Ukraine, as well as challenges that the Ukrainian education system is facing today. Primary research methods applied are as follows: comparative analysis of scientific research, observing and analytical methods such as analysis of statistical and secondary data, provided by domestic and foreign researchers.During the study, statistical data and literary sources related to the research topic were analysed. The strengths and weaknesses of the Ukrainian education system were identified. The most important threats identified include the russian invasion of Ukraine and the associated losses. The study determined that distance education is a trend in the world and has gained popularity in recent years due to the forced isolation of the population due to Covid-19. It was defined that Ukraine lacks a strong formalised system of distance education and a conscious focus on lifelong learning. Nevertheless, Ukraine has started to move in this direction. The main impediment is the military situation in the country, which causes underfunding and insufficient focus on the education sector, as well as a high level of risks for stakeholders and the overall educational crisis in the country.
Keywords: online education; distance learning; COVID-19; education system; education crisis; russian invasion